2021
DOI: 10.1002/jmv.27014
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccination hesitancy in patients with autoimmune diseases: A mystery that needs an immediate solution!

Abstract: We recently read articles addressing the concerns of patients with autoimmune disorders, highlighting a lack of evidence on the pros and cons of the newly developed coronavirus disease 2019 vaccines in this population. 1 On the other hand, this pandemic worsens day by day, with total confirmed cases reaching 123 million as of March 21, 2021, and a death toll of 2.7 million so far. 2,3 Dreadfully, most robust healthcare systems are finding it hard to cope with the pandemic of COVID-19. [4][5][6][7] The only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, other studies reported safety concerns among patients with IEI or AIIRDs. Some studies evaluated the specific patient concerns related to the COVID-19 vaccine, which included unknown long-term side effects, the newness of the COVID-19 vaccine, and the perception of rushed development and introduction with potential financial links to the pharmaceutical companies ( 9 , 18 , 24 , 26 ). Those unvaccinated also feared that the vaccine would be harmful and could cause thrombosis ( 24 ), despite well-documented contrary evidence ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies reported safety concerns among patients with IEI or AIIRDs. Some studies evaluated the specific patient concerns related to the COVID-19 vaccine, which included unknown long-term side effects, the newness of the COVID-19 vaccine, and the perception of rushed development and introduction with potential financial links to the pharmaceutical companies ( 9 , 18 , 24 , 26 ). Those unvaccinated also feared that the vaccine would be harmful and could cause thrombosis ( 24 ), despite well-documented contrary evidence ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported vaccine hesitancy in 13.4%, 19.4%, and 17.8% of patients with cancer, autoimmune diseases, and chronic lung diseases, respectively (6), despite expert opinions that the benefits of being vaccinated outweigh the limitations of available evidence for a specific high-risk group (7)(8)(9)(10). Moreover, vaccine resistance appears to correlate with geographic location, country-specific regulations of vaccines availability, the proposed vaccination schedule, study methodologies, the study period in relation to the pandemic wave, and evolving vaccine safety and efficacy data (1,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous nature of the systemic autoimmune diseases and the immunosuppressive therapy might lead to concerns of severe outcomes in these patients. Thus, the perception towards the vaccination and immunological response might vary compared to the general population (Ali et al, 2021;Gaur et al, 2021). The reservations to get vaccinated against COVID-19 might be especially apparent for these patients since there is no data available about the balance between benefits and risks of the newly developed COVID-19 vaccines in this population (Boekel et al, 2021;Eftimov et al 2021).…”
Section: Systemic Autoimmune Diseases and Covid-19mentioning
confidence: 99%
“…Evidence suggests that establishing clear communication strategies and protocols for the COVID-19 vaccination is challenging. Although it is apparent that vaccinations do not pose a more prominent danger than the infections themselves, healthcare providers and communities are still concerned about the potential risk of worsening autoimmune diseases owing to insufficient data [ 25 ]. Currently, there is limited data available on the benefits and risks of COVID-19 vaccines in patients with autoimmune diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%